Study protocol: a pragmatic, cluster-randomized controlled trial to evaluate the effect of implementation of the Truenat platform/MTB assays at primary health care clinics in Mozambique and Tanzania (TB-CAPT CORE) - Leukes, Vinzeigh; Hella, J.; Sabi, I.; Cossa, M.; Khosa, C.; Erkosar, B.; Mangu, C.; Siyame, E.; Mtafya, B.; Lwilla, A.; Viegas, S.; Madeira, C.; et al. (BMC infectious diseases, 2024)
In 2020, the WHO-approved Molbio Truenat platform and MTB assays to detect Mycobacterium tuberculosis complex (MTB) and resistance to rifampicin directly on sputum specimens. This primary health care center-based trial in Mozambique and Tanzania investigates the effect of Truenat platform/MTB assays (intervention arm) combined with rapid communication of results compared to standard of care on TB diagnosis and treatment initiation for microbiologically confirmed TB at 7 days from enrolment.